New Developments in Peritoneal Fibroblast Biology: Implications for Inflammation and Fibrosis in Peritoneal Dialysis. (1st October 2015) - Witowski, Janusz; Kawka, Edyta; Rudolf, Andras; Jörres, Achim
Abstract : Uraemia and long-term peritoneal dialysis (PD) can lead to fibrotic thickening of the peritoneal membrane, which may limit its dialytic function. Peritoneal fibrosis is associated with the appearance of myofibroblasts and expansion of extracellular matrix. The extent of contribution of resident peritoneal fibroblasts to these changes is a matter of debate. Recent studies point to a significant heterogeneity and complexity of the peritoneal fibroblast population. Here, we review recent developments in peritoneal fibroblast biology and summarize the current knowledge on the involvement of peritoneal fibroblasts in peritoneal inflammation and fibrosis.